Comparison of bone mineral density among pre- and post-menopausal women with and without chronic generalized periodontitis - Priyadarshini Ramasubramanian Svedha; Jaideep Mahendra; Ramakrishnan Theayarajar; Ambalavanan Namachivayam (Wolters Kluwer Medknow Publications, 2017)
Background: There have been a very limited number of studies regarding the assessment of bone mineral density (BMD) using dual energy X-ray absorptiometry scan. Hence, the purpose of the study was to assess the relationship between BMD and periodontal health in three different study groups. Materials and Methods: The study comprised of thirty female individuals who were categorized into three groups: ten premenopausal women with healthy periodontium (Group A), ten premenopausal women with generalized chronic periodontitis (Group B), and ten postmenopausal women with generalized chronic periodontitis (Group C). Number of teeth, plaque index, probing depth, clinical attachment level, interproximal alveolar bone loss, T-score for dual femur and posteroanterior (PA) spine, and BMD for dual femur and PA spine of each individual were recorded in all the three groups. Results: The BMD and T-score of dual femur and PA spine were found to be low in Group C when compared to Group A and B which was statistically significant. Conclusion: Postmenopausal women with generalized chronic periodontitis (Group C) exhibited severe periodontal destruction with less BMD. Hence, it is suggested that periodontitis may be a risk indicator for osteoporosis in postmenopausal women and vice versa.